Uso de la técnica del delineamiento del habla para cambiar la conducta verbal - Ottoni, Thais Maria (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Numerous studies have investigated the techniques of modifying verbal behavior. The present study presents the technique considered most important — the modeling of speech. This technique investigates the interference of another auditory stimulus, the voice of the experimenter, for the purpose of modifying the “inadequate” control of stimuli that occurs in stuttering. The effect of the experimenter’s voice is the model for the word or expression to be repeated, in sequence, by the subject. The subject observes the recording of his/her errors, the decrease of which serves as reinforcement.